2020
DOI: 10.1111/jcmm.15767
|View full text |Cite
|
Sign up to set email alerts
|

The neurofibromatosis type I gene promotes autophagy via mTORC1 signalling pathway to enhance new bone formation after fracture

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…However, to the best of our knowledge, few studies have reported the effects of NF1 on autophagy in BMSCs. Tan et al ( 20 ) revealed that autophagic activity and osteogenic differentiation were significantly enhanced in NF1 -overexpressing BMSCs, consistent with the results of the present study. However, Tan et al ( 20 ) only established NF1 -overexpression BMSC models, which are different from the clinical situation in patients with NF1 mutations, where the function of NF1 is insufficient ( 8 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, to the best of our knowledge, few studies have reported the effects of NF1 on autophagy in BMSCs. Tan et al ( 20 ) revealed that autophagic activity and osteogenic differentiation were significantly enhanced in NF1 -overexpressing BMSCs, consistent with the results of the present study. However, Tan et al ( 20 ) only established NF1 -overexpression BMSC models, which are different from the clinical situation in patients with NF1 mutations, where the function of NF1 is insufficient ( 8 ).…”
Section: Discussionsupporting
confidence: 93%
“…Tan et al ( 20 ) revealed that autophagic activity and osteogenic differentiation were significantly enhanced in NF1 -overexpressing BMSCs, consistent with the results of the present study. However, Tan et al ( 20 ) only established NF1 -overexpression BMSC models, which are different from the clinical situation in patients with NF1 mutations, where the function of NF1 is insufficient ( 8 ). Therefore, a cell model with inhibited expression of NF1 can simulate the pathological conditions of NF1 more closely compared with one with overexpression of NF1 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Zhao et al demonstrated that autophagy regulates hypoxia-induced osteoclastogenesis, and the activation of autophagy under hypoxic conditions is caused by the HIF-1 α -dependent upregulated expression of BNIP3 [ 15 ]. In neurofibromatosis type I (NF1) overexpressing BMSCs, NF1 overexpression promotes new bone formation after fracture by enhancing autophagy and inhibiting mTORC1 signaling, indicating that promoting autophagy can promote new bone formation [ 38 ]. Unfortunately, at present, we have not measured the mineral density of the femoral head and more autophagy-related proteins (such as p62); meanwhile, we cannot determine which active ingredients in Gujiansan exert a therapeutic effect on SANFH and which active ingredient or ingredients exert a regulatory effect on autophagy in SANFH.…”
Section: Discussionmentioning
confidence: 99%